Economic Crisis Influence on FDI and Foreign Inflows in Sub-Saharan Africa Economies - Odhiambo, Scholastica Achieng (European Scientific Journal, ESJ, 2017)
The global economic crisis affected most of developed economies in North America and Europe which was likely to trigger a trickle-down effects on Sub-Saharan Africa. This effect was characterized by falling exports demand, foreign capital inflows in terms of foreign direct investment (FDI), foreign aid inflows and remittances from African immigrants working in the ICs. This paper investigated the effects of economic crisis on FDI and the foreign aid inflows in four countries which include Botswana, Kenya, Malawi and Mozambique. Panel data was used for analysis with OLS, Random Effects and Maximum Likelihood Estimation from 1990-2010 was conducted. The results show that contrary to the expectation that economic crisis had negative effects on FDI inflows in SSA it was the other way round. Economic crisis has a positive impact on FDI inflows. This maybe because of natural resource oriented FDIs in Mozambique and Botswana and low integration in world markets for Kenya and Malawi (Most FDI are primary resource base such as agriculture).